2018
DOI: 10.5604/01.3001.0012.0482
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriotherapy for preventing recurrent upper respiratory infections in children: a real-world experience

Abstract: Background Recurrent upper respiratory infections (RURI) constitute a social problem for both their pharmaco-economic impact and the burden for the family. Bacteriotherapy could be an interesting preventive option. Objective The aim of this study was to evaluate the preventive effects of RURI in children. Design The study was designed as spontaneous, and was conducted in real-life seting. Globally, 80 children (40 males, mean age 5.26 (2.52) years) with RURI were enrolled. Children were treated with Streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…The fact that Streptococcus was found to be more prevalent in healthy controls in this study could be explained by a higher abundance of commensal species among nonasthmatic individuals, such as Streptococcus salivarius and Streptococcus oralis , which would maintain the stability of the community against pathogenic species. In fact, previous studies have shown that the administration of certain strains of both species via nasal spray reduced the occurrence of upper respiratory tract infections, significantly diminishing the occurrence of the episodes, as well as the number of school and work absences . Therefore, our results suggest that future studies are needed to understand whether topical administration of probiotics may effectively change the oral or lung microbiome and, consequently, become a new strategy in asthma management and/or prevention.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The fact that Streptococcus was found to be more prevalent in healthy controls in this study could be explained by a higher abundance of commensal species among nonasthmatic individuals, such as Streptococcus salivarius and Streptococcus oralis , which would maintain the stability of the community against pathogenic species. In fact, previous studies have shown that the administration of certain strains of both species via nasal spray reduced the occurrence of upper respiratory tract infections, significantly diminishing the occurrence of the episodes, as well as the number of school and work absences . Therefore, our results suggest that future studies are needed to understand whether topical administration of probiotics may effectively change the oral or lung microbiome and, consequently, become a new strategy in asthma management and/or prevention.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, previous studies have shown that the administration of certain strains of both species via nasal spray reduced the occurrence of upper respiratory tract infections, 33,34 significantly diminishing the occurrence of the episodes, as well as the number of school and work absences. 35 Therefore, our results suggest that future studies are needed to understand whether topical administration of probiotics may effectively change the oral or lung microbiome and, consequently, become a new strategy in asthma management and/or prevention. In contrast to the results obtained for Streptococcus, the genus Veillonella was found to be associated with higher risk for asthma, which is consistent with the differences observed in a previous study in the gut microbiome composition, focused on children at 1-year old that later developed asthma at the age of 5 years.…”
Section: Discussionmentioning
confidence: 93%
“…Nasal administration of a mixture containing Streptococcus salivarius 24SMB and Streptococcus oralis 89a was correlated with a reduction in the number of RRIs compared to the previous year (2.75 vs 5.98 episodes/year, p = 0.0001), the number of school days (2.80 vs 4.50 days/month, p = 0.0001) and workdays lost (1.48 vs 2.33 days/month, p = 0.0001) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Такой подход повышает трансформацию полученной энергии к поврежденным тканям. Это объясняет отдельные моменты пусковых звеньев биофизических, физико-химических и биологических процессов, связанных с возбуждением или нагреванием тканей, определяющих специфичность их лечебных эффектов [50,51].…”
Section: Introductionunclassified